Polymerase chain reaction‐positivity and predictors for SARS‐CoV‐2 infection among diagnosed cases' in North West Ethiopia - Fassikaw Kebede; Tsehay Kebede (Health Science Reports, 2023)
Abstract Background The lack of sophisticated diagnosing equipment for polymerase chain reaction (PCR) during the incidence of variant types of COVID‐19 underestimates the morbidity and mortality patterns of this pandemic. Thus, this study aimed to estimate seropositive and confirmatory predictors for COVID‐19 suspected and tested cases through polymerase chain reaction (RT‐PCR) in two diagnosing Methods A facility‐based descriptive cross‐sectional study was employed among COVID‐19 suspected cases from January 2, 2022, to June 9, 2022. The data were collected both using a structured interviewees and nasopharyngeal (NP) swabs. The nasal swab (NS) was analyzed in the laboratory for RNA detection of the virus using PCR. The collected data were entered into Epi Data version 4.2 and then exported to STATA (SE) version R‐14 software for further analysis. multivariable logistic regression was used to assess the associated risk Results A total of 285 suspected cases have participated in this study. The overall mean (±SD) age of the participants was 37.5 (±18.5) years. The majority, 174 (61.1%) of the tested groups were symptomatic when diagnosed. The positivity of RT‐PCR for suspected and COVID‐19 diagnosed cases were confirmed in 62/285 (21.75%). In multivariable analysis, they were aged 26–50 years (adjusted odds ratio [AOR] = 4.2, 95% confidence interval [CI] = 1.5–10.75), had comorbidity (AOR = 5.8; 95% CI = 2.1–12.2), and cigarette smokers (AOR = 13.5; 95% CI = 5.3–36.6) were significantly associated with developing COVID‐19 infection. Conclusion More than two in every nine suspected cases were positive RT‐PCR tests, and the infectivity of COVID‐19 was significantly associated with age 25–50 years, comorbidities, and cigarette smoking. The deployment of high‐quality diagnostic kits like RT‐PCR is crucial for the early detection and risk stratification of suspected cases.